2012
DOI: 10.1162/jocn_a_00137
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Face-specific Cortical Activity in the Complete Absence of Awareness: Converging Evidence from Functional Magnetic Resonance Imaging and Event-related Potentials

Abstract: Abstract■ In this study, we explored the neural correlates of perceptual awareness during a masked face detection task. To assess awareness more precisely than in previous studies, participants employed a 4-point scale to rate subjective visibility. An eventrelated fMRI and a high-density ERP study were carried out. Imaging data showed that conscious face detection was linked to activation of fusiform and occipital face areas. Frontal and parietal regions, including the pre-SMA, inferior frontal sulcus, anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 95 publications
5
24
0
Order By: Relevance
“…First, activity reflecting the attentional shifting to the lateralized target was markedly reduced for unaware trials, as reflected by a reduced N2pc component beginning at 180 ms. Concurrently, a lateralized negativity with a distribution similar to the previously characterized visual awareness negativity (VAN, present for images that were seen and not those unseen) (Rodriguez et al, 2012) was reduced here in cases of unawareness. However, as noted above, this response is likely a convolution of the VAN and face-specific negativity, both of which are reduced in cases of unawareness (Figure S1).…”
Section: Discussionsupporting
confidence: 69%
“…First, activity reflecting the attentional shifting to the lateralized target was markedly reduced for unaware trials, as reflected by a reduced N2pc component beginning at 180 ms. Concurrently, a lateralized negativity with a distribution similar to the previously characterized visual awareness negativity (VAN, present for images that were seen and not those unseen) (Rodriguez et al, 2012) was reduced here in cases of unawareness. However, as noted above, this response is likely a convolution of the VAN and face-specific negativity, both of which are reduced in cases of unawareness (Figure S1).…”
Section: Discussionsupporting
confidence: 69%
“…An alternative route that bypasses the visual ventral temporal pathway has been proposed for fast processing of this type of stimuli [21]. The existence of such a pathway in processing affective stimuli in humans has been questioned by others who suggest that the visual pathway may be sufficient for fast processing of these stimuli – even with reduced attentional resources and awareness – and, further, propose a role for top-down biasing of visual cortex involving frontal-parietal regions [22][24]. An alternative direct frontal-occipital pathway has been proposed to explain unconscious face processing in normal cognition and covert recognition in prosopagnosics [25].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence that unseen stimuli undergo some unconscious processing in the primary and selective visual areas [21] as well as the amygdala [22] has previously been taken to imply that activity per se in these areas is not sufficient for conscious access. However, a recent study has shown that FFA activation to faces may in itself be a correlate of aware perception [23]. In the case of the amygdala as well, support for the notion that its activation is related to aware perception is growing [17].…”
Section: Discussionmentioning
confidence: 99%